Remanentes socio-históricos y culturales de la esclavitud urbana en el centro Histórico La Habana Vieja - Portuondo Cárdenas, Inaury (Comparative Cultural Studies: European and Latin American Perspectives, 2018)
Transatlantic slavery as a process has been stereotyped in many bibliographies emphasizing plantation slavery. However, urban slavery and its characteristics are always overlapping “under the city’s comfort” that the owners could offer. In the Havana Historic Center, this view has a great impact on the history, culture and development of a city close to its 500th anniversary. However, the optimal visualization and socialization of the subject with its just historical treatment has been a debt for the management of heritage in terms of the slave theme. The architectural potentialities, popular traditions and other expressing that exist in Old Havana, has its genesis in the period of slavery in Cba. However, repeated discourses polarize only African-based religious practices as the most transcendental legacy of Africans to Havana and Cuban culture. To approach the historical elements related to urban slavery, to Africans and descendants as active subjects in the formation of a transculturated society; it confirms how cultural resistance was the most effective weapon from black people. This article systematically links the contributions made by previous investigations regarding urban slavery and as a contribution the sites related to this trend that persist as witnesses in an old and rich city stand out.